The Effectiveness of Internal Control Tested by The Characteristics ‎of The Company and Its Manager: A Study Carried Out on A Sample of Moroccan Companies Listed on The Casablanca Stock Ex‎change - Tamiri, Mohamed Anis; Cherkaoui , Mariem; Idrissi , Nabaouia; Redouane , Kaiss; Fikri , Yahya; Nassiri , Asmaa (International Journal of Accounting and Economics Studies, 2025)
Following the multiple accounting and financial scandals that have shaken the American and European stock markets, several measures have ‎been taken by the public authorities to improve financial transparency, ensure the security of savers and investors, and restore confidence in the financial markets. At the organizational level, the Committee on Sponsoring Organizations of the Treadway ‎Commission (COSO) has proposed a framework to ensure that assets are protected and that all of the company's activities comply with its ‎policies and procedures.‎The characteristics of the manager and the company play an important role. This paper seeks to examine the effect of the characteristics of ‎the company and its manager on the effectiveness of internal control. It presents the results of a study carried out on a sample of 36 Moroccan companies listed on the Casablanca Stock Exchange to test the empirical validity of the hypotheses formulated following a literature ‎review. The regression results confirm the positive effect of firm size, age, and financial health as the main characteristics of the firm on the ‎effectiveness of internal control. On the other hand, the effect of manager characteristics remains mixed due to the family nature of listed ‎Moroccan firms‎.
Keywords: Internal Control Effectiveness; Business Characteristics; Financial Health; Chief Executive Officer Age; Entrenchment. T